KEBIJAKAN DAERAH SEBAGAI LANDASAN PELAKSANAAN OTONOMI DAERAH - Maranjaya, Abdul Kahar (Al-Qisth Law Review, 2017)
Decentralization is the delegation of authority to make decisions and policies to the manager or the people at the lower levels of an organization in the area of autonomy decisions are trimmed, just at the local level that save energy and money. In the concept of decentralization of the central government still has a role as a conduit of the budget through the budget deconcentration will be up to the province. Logically deconcentration will decrease along with the increasing decentralization of funds. In practical terms it is manifested in its merger phenomenon regional offices ministries to local governments. Enforced vertical pattern of deconcentration is embodied in the pattern of deconcentration in the provincial government is still funded by the center. Based on this reality, the criteria for transfer of funds from the central government to the regions is important.